Design and implementation of software router supporting segment routing - Xiaomin GAO; Xuejing LIU; Jiawei LI; Hongbin LUO; Ping DONG (Dianxin kexue)
Segment routing (SR) is a routing mechanism proposed by IETF in recent years,which aims to make the IP/MPLS network service-oriented and more efficient.SR eliminates the complex control plane protocol (LDP/RSVP-TE) of the MPLS network,while SR implements the traffic engineering mechanism.Different from the explicit path in the RSVP tunnel which maintains the state of each flow in the middle of the tunnel,the explicit path based on SR only maintains the state of flow at the entrance border router of the SR domain.For this reason,SR improves the scalability of the network.Therefore the research of the SR mechanism is very important to the next generation internet.The realization mechanism of SR was studied,using the click router.The SR control plane subsystem based on PCE architecture and each module of MPLS-based SR data plane subsystem were implemented and deployed in practice to verify the feasibility of the software router in actual deployment.